"Help is where you find it": The role of weak ties networks as sources of information and support in virtual health communities. (19th November 2018) - Zigron, Shimrit; Bronstein, Jenny
Abstract : Virtual health communities allow people with health‐related concerns to engage in supportive communication with individuals coping with similar problems that would be difficult or impossible to form in the face‐to‐face world. This study examined the information interactions in an Israeli virtual health community on Facebook dealing with ulcerative colitis and Crohn's disease drawing from the "weak ties" network theory as a theoretical framework. Weak ties are social ties or acquaintances that can function as an important source for diversified experiential information and emotional support, reducing stigma and providing a sense of belonging. The study consisted of 23 semistructured interviews with registered members of the group. Findings of this study parallel the four functions of weak ties by allowing chronically ill patients: access to diverse sources of information including experiential information from others suffering from the same illness; the possibility to disclose personal information reducing fear from stigma or rejection; and a sense of belonging.